Method for preparing nano CaCO3 from carbide slag
Through the phase transfer reaction of calcium carbide slag and carbonization precipitation reaction, combined with crystal form control agent, an efficient and environmentally friendly nano CaCO3 preparation efficiency and resource waste in the existing technology are solved, and high additional Value the production and environmentally friendly "waste control" process of products.
Patent Information
- Application Number
- CN202411491286.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to efficiently prepare high-quality nano CaCO3 on industrial scale, especially at high initial Ca2+ concentrations, and the calcium carbide slag resources are not effectively utilized, resulting in waste of resources and environmental pollution.
Calcium slag is used as raw material, and Ca elements are extracted by phase transfer reaction and carbonization precipitation reaction, and the Ca elements are extracted by complexing agent or chelating agent, and nano CaCO3 with small particle size and uniform particle size are prepared by carbonization method under the action of crystal form control agent. The industrial waste gas CO2 is used as the carbonizing agent to achieve the process of "use waste to control waste".
The efficient preparation of nano CaCO3 with particle size of 20~40nm has been achieved, which improves the added value and production efficiency of the product, reduces production costs, and has a gentle and environmentally friendly process, which is in line with the economic cycle development strategy and the "dual carbon" goal.
Smart Images

Figure CN119306242A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technology of recycling industrial solid waste resources, and specifically relates to the technical field of high-value utilization of carbide slag, and in particular to a method for preparing nano-CaCO3 from carbide slag. Background Art
[0002] Nano-CaCO3 is widely used as an inorganic filler in rubber, plastic, coating, papermaking and other industries due to its obvious advantages in reinforcement, transparency and dispersibility. my country is a major consumer and producer of CaCO3 resources in the world. Although the total production of nano-CaCO3 has reached 2 million tons / year, there is still a significant gap with the advanced level of foreign countries in terms of product quality, product performance and comprehensive cost control. High-quality high-end nano-CaCO3 products still need to be imported in large quantities. With the rapid development of industries such as rubber and plastics, the demand for nano-calcium carbonate has increased rapidly, and higher requirements have been put forward for the performance indicators of nano-calcium carbonate such as particle size and oil absorption value. Therefore, the preparation of ultra-fine, uniform particle size and high-activity nano-calcium carbonate has become a research hotspot.
[0003] Calcium carbide slag is a byproduct of acetylene production from calcium carbide, with the main component being Ca(OH)2 (about 90%). my country produces about 20 million tons of calcium carbide slag each year, with a cumulative stockpile of more than 100 million tons. If it is not properly utilized, it will not only occupy a large amount of land, cause serious pollution to the surface environment and groundwater system, but also waste precious resources.
[0004] At present, carbide slag is mainly used in the fields of building materials (such as brick making, building putty, etc.), environmental protection (such as acid wastewater treatment, flue gas desulfurization, etc.); in the chemical industry, it is used to produce cement, replace slaked lime in the production of propylene oxide, soda ash and potassium chlorate, and prepare light CaCO3, etc. But overall, the added value of the products is low and the technology is not very advanced.
[0005] The preparation of nano-CaCO3 mainly includes Ca(OH)2-H2O-CO2, Ca 2+ -H2O-CO2 two types of reaction systems, in which Ca 2+ -H2O-CO2 reaction system can produce nano-CaCO3 products with high purity and uniform particle size. However, due to the extremely fast reaction speed of this system and the difficulty in controlling the process conditions, it can only be produced at a low initial Ca 2+ Concentration (about 0.1 mol·L -1 ) is not convenient for industrial-scale production.
[0006] Therefore, carbide slag is used as raw material and industrial waste gas CO2 is used as carbonizing agent. 2+ -H2O-CO2 reaction system, higher initial Ca 2+ Concentration (about 1 mol·L-1 ) to prepare nano-CaCO3, realizing “treating waste with waste and turning waste into treasure”, which is in line with the national economic circulation development strategy of bulk industrial solid waste and the “dual carbon” strategic goal. Summary of the invention
[0007] The main purpose of the present invention is to propose a method for preparing nano-CaCO3 from carbide slag, aiming to provide a method for efficiently preparing nano-CaCO3 by using industrial solid waste carbide slag as raw material and making full use of waste resources.
[0008] To achieve the above object, the method of the present invention uses carbide slag as raw material to prepare nano-CaCO3, comprising the following steps: S1, phase transfer reaction stage: prepare a phase transfer agent solution of a certain concentration, then add carbide slag (the main component is Ca(OH)2, dry basis content 80~95%), react under stirring, filter to obtain a certain concentration of Ca 2+ The phase transfer liquid of the present invention has a concentration (the main component is CaY solution); the carbide slag is the carbide slag dried at 100-120°C.
[0009] S2, carbonization precipitation reaction stage: dilute the phase transfer liquid obtained by filtration with deionized water to obtain Ca 2+ Concentration is 0.8~1.5mol·L -1 Add the crystal control agent and ammonia water to the carbonized precipitation raw material liquid, pass CO2, stir and react until the pH value is 7.5-9.0, filter, wash and dry after the reaction to obtain nano-CaCO3. (According to the law of conservation of mass, the Ca in the carbonized precipitation raw material liquid is 2+ The theoretical yield of nano-CaCO3 that can be obtained by all precipitation is used as the calculation basis to calculate the addition amount of component 1 and component 2 of the crystal shape control agent); Wherein, the phase transfer agent is Ca 2+ The complexing agent or chelating agent, the crystal shape control agent includes component one and component two.
[0010] Preferably, after filtering for solid-liquid separation in step S2, the main component of the filtrate is the solution of the phase transfer agent, which is returned to step S1 for recycling; the filter cake obtained is washed and dried to obtain a nano-CaCO3 sample. The ammonia water used is commonly used industrial ammonia water with a concentration of generally 25-28wt%.
[0011] The present invention uses carbide slag as raw material and complexing agent or chelating agent as phase transfer agent to extract Ca element in carbide slag, and adopts carbonization method under the action of crystal control agent to prepare high-quality nano-CaCO3 with small particle size (20-40nm) and uniform particle size and good dispersibility.
[0012] Preferably, in step S1, the concentration of the phase transfer agent solution is 1-3 mol·L-1 ; The molar ratio of Ca(OH)2 to the phase transfer agent in the carbide slag is 2:3-6:3.
[0013] Preferably, in step S1, the phase transfer agent includes one or two of citric acid and its salts, glucose and its salts, sodium succinate, L(+)-sodium tartrate, sodium oleate, sodium laurate, sodium salicylate, sodium alginate, succinic acid, DL-malic acid, and sucrose.
[0014] Preferably, in step S1, the stirring rate is 200-600 rpm; Preferably, in step S1, the reaction time is 10 to 100 minutes.
[0015] Preferably, in step S2, the crystal shape control agent includes component one and component two, wherein component one includes any one of oleic acid, glycerol, glycerol, pentaerythritol, polyethylene glycol, phenylalanine, triethoxysilane, hydroxyethyl dimethacrylate, and tetrabutyl titanate, and component two includes any one of aluminum nitrate, magnesium chloride, ammonium carbonate, aluminum sulfate, and ammonium acetate.
[0016] Preferably, the addition amount of the component one and the component two is based on the amount of Ca in the carbonization precipitation raw material solution. 2+ The theoretical amount of nano-CaCO3 that can be obtained by all precipitation is used as a basis, and the addition amount of the component one is 1-7%, and the addition amount of the component two is 1-7%.
[0017] Preferably, in step S2, the stirring rate is 200-600 rpm; The reaction temperature is 5-35°C.
[0018] Preferably, in step S2, the nano-CaCO3 is a pure phase calcite crystal, the average particle size of the nano-CaCO3 is 20-40 nm, and the specific surface area of the nano-CaCO3 is 20-35 m 2 ·g -1 The oil absorption value of the nano-CaCO3 is 35-40 g·g -1 The main performance indicators are better than the technical indicators of Type II nano-CaCO3 for rubber in "Nano Calcium Carbonate" (GB / T19590-2023).
[0019] Preferably, in step S2, the flow rate of CO2 is 0.1-0.6 L·min -1 .
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with the existing nano-CaCO3 preparation technology, the present invention uses carbide slag as raw material, complexing agent or chelating agent as phase transfer agent, and adds an appropriate amount of crystal shape control agent to prepare nano-CaCO3 with an average particle size of 20-40 nm, which is conducive to the development of high value-added products of carbide slag; and the CaY concentration in the reaction system is relatively high (about 1 mol∙L -1 ), with higher production efficiency.
[0021] (2) The phase transfer agent used in the present invention includes one or two of citric acid and its salts, glucose and its salts, sodium succinate, L(+)-sodium tartrate, sodium oleate, sodium laurate, sodium salicylate, sodium alginate, succinic acid, DL-malic acid, and sucrose, which can better react with Ca 2+ Complexation or chelation is carried out so that the Ca element in carbide slag can be extracted to a greater extent. In addition, this process adopts a circulating process and makes full use of phase transfer agents, which greatly reduces production costs.
[0022] (3) The crystal shape control agent used in the present invention includes component one and component two. Component one is one of oleic acid, glycerol, propylene glycol, pentaerythritol, polyethylene glycol, phenylalanine, triethoxysilane, hydroxyethyl dimethacrylate, and tetrabutyl titanate. Component two is one of aluminum nitrate, magnesium chloride, ammonium carbonate, aluminum sulfate, and ammonium acetate. It can effectively inhibit the growth of CaCO3 particles. The prepared nano-CaCO3 has a small particle size, uniform particle size, and good dispersibility.
[0023] (4) The present invention also has the advantages of mild process conditions and green environmental protection. The process uses industrial waste gas CO2 as a carbonizing agent, "treating waste with waste and turning waste into treasure", which is in line with the economic cycle development strategy and the "dual carbon" strategic goals. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The schematic diagram of the process of preparing nano-CaCO3 using carbide slag as raw material in the present invention; Figure 2 This is the XRD diagram of the nano-CaCO3 product prepared in Example 1 of the present invention; Figure 3 This is a STEM image of the nano-CaCO3 product prepared in Example 1 of the present invention; Figure 4This is a SEM image of the nano-CaCO3 product prepared in Example 1 of the present invention; Figure 5 This is a SEM image of the nano-CaCO3 product prepared in Example 2 of the present invention; Figure 6 This is a SEM image of the nano-CaCO3 product prepared in Example 3 of the present invention; Figure 7 This is a SEM image of the nano-CaCO3 product prepared in Comparative Example 1 of the present invention; Figure 8 This is a SEM image of the nano-CaCO3 product prepared in Comparative Example 2 of the present invention; Fig. 9 This is a SEM image of the nano-CaCO3 product prepared in Comparative Example 3 of the present invention; Fig.10 This is the SEM image of the nano-CaCO3 product prepared in Comparative Example 4 of the present invention.
[0026] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0027] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0028] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention. Example 1
[0029] A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 1.5 mol·L -1100 mL of sodium citrate phase transfer agent solution was measured and placed in a beaker, and 9.25 g of carbide slag (calculated as 90% of Ca(OH)2, the same below. The molar ratio of Ca(OH)2 to phase transfer agent in this example is 4:3) was added, and the reaction was stirred at room temperature for 25 minutes. The insoluble impurities (mainly carbon black, aluminum hydroxide, iron hydroxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 1.2 mol·L -1 of phase transfer liquid.
[0030] (2) Take 100 mL of the above phase transfer liquid and add it to 20 mL of deionized water, add 0.15 g of phenylalanine, 2 mL of ammonia water and 0.15 g of aluminum nitrate, mix well, and then introduce CO2 at 15 ° C and 600 rpm to react until the pH value is 7.90; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 30 nm and uniform particle dispersion. Example 2
[0031] A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 1.2 mol·L -1 100 mL of sodium succinate phase transfer agent solution was measured and placed in a beaker, 13.70 g of carbide slag was added (the molar ratio of the feed was 4:5), and the mixture was stirred at room temperature for 35 min. The insoluble impurities (mainly carbon black, aluminum hydroxide, iron hydroxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 1.5 mol·L -1 of phase transfer liquid.
[0032] (2) Take 100 mL of the above phase transfer liquid and add it to 25 mL of deionized water, add 0.22 g of phenylalanine, 2 mL of ammonia water and 0.22 g of magnesium chloride, mix well, and then introduce CO2 at 10 ° C and 600 rpm to react until the pH value is 8.5; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 35 nm and uniform particle dispersion. Example 3
[0033] A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 1.2 mol·L -1100 mL of sucrose phase transfer agent solution was measured and placed in a beaker, and 8.22 g of carbide slag (molar ratio of feed was 4:3) was added, and the mixture was stirred at room temperature for 20 min. The insoluble impurities (mainly carbon black, iron oxide, aluminum oxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 0.9 mol·L -1 of phase transfer liquid.
[0034] (2) Take 100 mL of the above phase transfer liquid and add it to 13 mL of deionized water, add 0.09 g of hydroxyethyl dimethacrylate, 2 mL of ammonia water and 0.18 g of aluminum sulfate, mix well, and then introduce CO2 at 15 ° C and 600 rpm to react until the pH value is 7.8; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 40 nm and uniform particle dispersion.
[0035] Comparative Example 1 A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 2 mol·L -1 100 mL of sodium salicylate phase transfer agent solution was measured and placed in a beaker, 12.33 g of carbide slag (the molar ratio of the feed was 10:7) was added, and the mixture was stirred at room temperature for 40 min. The insoluble impurities (mainly carbon black, aluminum hydroxide, iron hydroxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 1.2 mol·L -1 of phase transfer liquid.
[0036] (2) Take 100 mL of the above phase transfer liquid and add it to 10 mL of deionized water, add 5 mL of ammonia water and 0.205 g of ammonium acetate, mix well, and then introduce CO2 at 20°C and 500 rpm to react until the pH value is 8.3; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 121.8 nm. The morphology is mostly rice-like and irregular in size.
[0037] Comparative Example 2 A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 1.5 mol·L -1100 mL of sodium alginate phase transfer agent solution was measured and placed in a beaker, 9.25 g of carbide slag (molar ratio of feed was 4:3) was added, and the mixture was stirred at room temperature for 25 min. The insoluble impurities (mainly carbon black, aluminum hydroxide, iron hydroxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 1.2 mol·L -1 of phase transfer liquid.
[0038] (2) Take 100 mL of the above phase transfer liquid and add it to 20 mL of deionized water, add 2 mL of ammonia water, mix well, and then introduce CO2 at 15°C and 600 rpm to react until the pH value is 7.90; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 120 nm, and is rice-grain or spindle-shaped with irregular size.
[0039] Comparative Example 3 A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 1.5 mol·L -1 100 mL of sodium citrate phase transfer agent solution was measured and placed in a beaker, 9.25 g of carbide slag (molar ratio of feed was 4:3) was added, and the mixture was stirred at room temperature for 25 min. The insoluble impurities (main components were carbon black, aluminum hydroxide, iron hydroxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 1.2 mol·L -1 of phase transfer liquid.
[0040] (2) Take 100 mL of the above phase transfer liquid and add it to 20 mL of deionized water, add 0.15 g of phenylalanine and 2 mL of ammonia water and mix well, then introduce CO2 at 15 ° C and 600 rpm stirring conditions to react until the pH value is 7.90; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 85 nm, uneven distribution, and more large particles.
[0041] Comparative Example 4 A method for preparing nano-CaCO3 comprises the following steps: (1) Prepare 1.5 mol·L -1100 mL of sodium citrate phase transfer agent solution was measured and placed in a beaker, 9.25 g of carbide slag (molar ratio of feed was 4:3) was added, and the mixture was stirred at room temperature for 25 min. The insoluble impurities (main components were carbon black, aluminum hydroxide, iron hydroxide, etc.) in the reaction solution were removed by suction to obtain Ca 2+ The concentration is 1.2 mol·L -1 of phase transfer liquid.
[0042] (2) Take 100 mL of the above phase transfer liquid and add it to 20 mL of deionized water, add 0.15 g of aluminum nitrate and 2 mL of ammonia water and mix well, then introduce CO2 at 15 ° C and 600 rpm stirring conditions to react until the pH value is 7.90; filter the carbonized liquid, and the main component of the filtrate is the solution of the phase transfer agent, which is returned to step (1) for recycling; the filter cake is washed and dried to obtain a nano-CaCO3 sample. The prepared nano-CaCO3 is a pure phase calcite crystal with an average particle size of 40 nm, but the agglomeration phenomenon is serious.
[0043] Test methods and results The morphology of the sample of Example 1 was determined by X-ray diffraction, and the Figure 2 ; The sample morphology of Example 1 was observed using a scanning transmission electron microscope, and the Figure 3 The particle size and morphology of the samples of Examples 1 to 3 and Comparative Examples 1 to 4 were observed using a SU8020 scanning electron microscope manufactured by Hitachi, Japan. Figures 4 to 10 Before the test, the sample was ultrasonically dispersed with ethanol for 30 minutes, dropped on the cleaned silicon wafer with a dropper, and tested after surface gold spraying treatment, with an accelerating voltage of 15 kV.
[0044] Depend on Figure 2 It can be seen that all the strong and sharp diffraction peaks in the XRD pattern of the nano-CaCO3 sample can be indexed as calcite crystal-type CaCO3 (JCPDS05-0586), and there is no obvious impurity diffraction peak, indicating that the prepared sample is a pure phase calcite crystal-type nano-CaCO3; Figure 3 It can be seen that the sample prepared in the embodiment of the present invention is granular and has a relatively uniform particle size. Figures 4 to 6 It can be seen that the particle size of the sample particles prepared in Examples 1 to 3 of the present invention is 20 to 40 nm, and the particle size is relatively uniform, and the product quality grade is high; Figures 7 to 10 It can be seen that the particle sizes of the sample particles prepared in Comparative Examples 1 to 4 are 40 nm to 121.8 nm, respectively, the sizes are irregular, and the product quality is not high.
[0045] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A method for preparing nano-CaCO3 from carbide slag, characterized in that: The method uses carbide slag as raw material and comprises the following steps: S1, prepare a phase transfer agent solution of a certain concentration and then add carbide slag, react under stirring, and filter to obtain a phase transfer liquid; S2, dilute the phase transfer liquid with deionized water to obtain Ca 2+ Concentration is 0.8~1.5mol·L -1 Add the crystal shape control agent and ammonia water to the carbonized precipitation raw material liquid, introduce CO2, react under stirring until the pH value is 7.5-9.0, filter, wash and dry after the reaction to obtain nano-CaCO3; Wherein, the phase transfer agent is Ca 2+ The complexing agent or chelating agent, the crystal shape control agent includes component one and component two.
2. The preparation method according to claim 1, characterized in that In step S1, the Ca of the phase transfer solution 2+ Concentration is 1~3 mol·L -1 ; The molar ratio of Ca(OH)2 to the phase transfer agent in the carbide slag is 2:3-6:
3.
3. The preparation method according to claim 1, characterized in that: In step S1, the phase transfer agent includes one or two of citric acid and its salts, glucose and its salts, sodium succinate, L(+)-sodium tartrate, sodium oleate, sodium laurate, sodium salicylate, sodium alginate, succinic acid, DL-malic acid, and sucrose.
4. The preparation method of nano-CaCO3 as claimed in claim 1, characterized in that: In step S1, the stirring rate is 200-600 rpm.
5. The preparation method according to claim 1, characterized in that: In step S1, the reaction time is 10 to 100 minutes.
6. The preparation method according to claim 1, characterized in that: In step S2, component one of the crystal shape control agent is any one of oleic acid, glycerol, propylene glycol, pentaerythritol, polyethylene glycol, phenylalanine, triethoxysilane, hydroxyethyl dimethacrylate, tetrabutyl titanate, etc., and component two is any one of aluminum nitrate, magnesium chloride, ammonium carbonate, aluminum sulfate, ammonium acetate, etc.
7. The preparation method according to claim 6, characterized in that: In step S2, the addition amount of component 1 and component 2 of the crystal shape control agent is about 1:10 ... 2+ The theoretical amount of nano-CaCO3 that can be obtained by all precipitation is used as a basis, and the addition amount of the component one is 1-7%, and the addition amount of the component two is 1-7%.
8. The preparation method according to claim 1, characterized in that: In step S2, the stirring rate is 200-600 rpm and the reaction temperature is 5-35°C.
9. The preparation method according to claims 1 to 8, characterized in that: In step S2, the prepared nano-CaCO3 is a pure phase calcite crystal, the average particle size of the nano-CaCO3 is 20-40 nm, and the specific surface area of the nano-CaCO3 is 20-35 m 2 ·g -1 The oil absorption value of the nano-CaCO3 is 35-40 g·g -1 .
10. The preparation method according to claim 1, characterized in that: In step S2, the flow rate of CO2 is 0.1~0.6L·min -1 .